The COVID-19 pandemic as an opportunity for a new humanism - Montalvo Jääskeläinen, Federico de (Razón y fe, 2020)
The pandemic caused by the SARS-CoV-2 virus has come to alter our reality in an extremely disruptive way. That alteration goes beyond health, and it´s affecting many other areas, such as the family, and the social, economic, professional, cultural and even political area. However, the shocking experience that we are living also opens the door to a new humanism, which puts human beings and their dignity at the center of the reflection and decision, and all of this, without neglecting the possibilities offered by biological and technological improvements. A new humanism where biotechnological advances will be for all the “human family”.